Tinjauan Literatur Sistematis Tentang Jam Kerja Dan Absensi Karena Sakit - Kusnani Sita Handayu; Ponco Trapsilo Widagdo; Saptawati Rita K; Rahmad Febriandi; Nofriwarti (OGZ Research & Publishing, 2023)
Seventy per cent of Indonesia's total population are workers. Labour productivity and employee survival are greatly influenced by employee health. Workplace health promotion is an important part of corporate health care and an essential part of maintaining and improving employee health. Survey results show that workplace health promotion has an impact on employee health, with healthy employees losing very few working days due to illness. The purpose of this study is to determine the relationship between working hours and sickness absence: Is a high number of working hours associated with better or worse health? There was insufficient evidence to support an association between sickness absence and part-time work or working hours. This non-significant finding may be due to heterogeneity in the operationalisation of key variables. On the other hand, the evidence in favour of a negative relationship between long working hours and sickness absence is strong. This relationship can be explained by (1) the healthy worker effect, (2) attendance motivation, and (3) differences in job characteristics. However, empirical testing for these explanations is still very limited. The authors' findings suggest that employers need to monitor employee health, especially during times of high/increased work pressure, even when sickness absence is low. Keywords : working time, hours worked, overtime, part-time, sickness absence